Analisis Studi Kelayakan Bisnis UMKM di Bidang Pangan pada Usaha Corn Dog Mozzarella dan Sosis - Nadya Andayani; Sri Wahyuni; Suhairi Suhairi (VISA: Journal of Vision and Ideas, 2022)
The declining economic situation during the pandemic made people’s livelihoods unstable, forcing people to be even more creative in opening business to carry on their fields or opening their own businesses to carry on their lives so that unemployment did not increase too much. By opening a small business such as corn dog an mozzarella sausage. The community’s economy will be helped and reduce the increase in unemployment during the current pandemic. Not only can it lift the community’s economy, the food sold must also have nutritional value so that countries affected by the pandemic are protected form other diseases. An example of this culinary corn dog. Nowadays, corndog culinary is widely known in Indonesia and its trends. Where corndog is one of the healthiest foods in the world after olive oil and this food comes from korea. This food is healthy because it is made from vegetables and there are also various kinds of nutrient and nutrients contained in it which are good for the health of the body. During a pandemic, people also need nutritious food. Keywords. Business feasibility, culinary corn dog mozzarella and sausage an economic aspects